STUDY ON OPTIMISATION OF EXTRACTION PROCESS OF TANSHINONE ⅡA AND ITS MECHANISM OF INDUCTION OF GASTRIC CANCER SGC7901 CELL APOPTOSIS - Hou, Jianhong; He, Jiantai; Jin, Xin; Hu, Tian; Zhang, Yangde (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to investigate the extraction process of tanshinone ⅡA and its mechanism of induction of gastric cancer SGC7901 cell apoptosis. Extraction process of tanshinone ⅡA was optimised by orthogonal experimental method, and its effect on gastric cancer SGC7901 cell apoptosis was observed using MTT assay and electron microscopy. The optimum extraction process of tanshinone ⅡA was as follows: addition of a 10-fold amount of 80% ethanol, one-time extraction, and extraction time of 45 minutes. The study concluded that tanshinone ⅡA can induce apoptosis of gastric cancer SGC7901 cells.